EFFECT OF SILICON, CALCIUM AND BORON ON APPLE LEAF MINERALS CONTENT - & Joody, Saleem (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This experiment was carried out at the apple orchard - College of Agricultural Engineering Science - University of Baghdad during the growing seasons 2017 and 2018. A factorial experiment was conducted within a Randomized Complete Block Design using three replicates and two factors, factor (S) which stands for trees sprayed with potassium silicate as a source of silicon at four levels (0, 2, 4 and 6 ml L-1), while factor (C) represents trees sprayed with a Calcium and Boron combination using three concentrations (0, 0.5 g L-1 Ca-EDTA +10 mg L-1 B, and 1 g L-1 Ca-EDTA+20 mg L-1 B). Main results showed that silicon had a significant effect on Nitrogen, Phosphorus, Potassium, Calcium, Boron, and Silicon, especially concentrations 4 and 6 ml L-1 for both seasons, Calcium Boron combination also affected studied traits specially treatment (1 g calcium + 20 mg L-1 boron) for both seasons, also the dual interaction treatment S3C3 and S4C3 gave the highest rates for most studied characteristics for both seasons.